ΤΥΧΕΣ ΤΗΣ ΑΠΟ 5-9-1816 ΕΠΙΣΤΟΛΗΣ TOΥ Α. ΚΟΡΑΗ (ΜΟΛΙΕΡΟΣ, ΚΟΚΚΙΝΑΚΗΣ, ΣΚΥΛΙΤΣΗΣ ΚΑΙ ΛΙΘΟΓΡΑΦΟΣ) - ΣΚΛΑΒΕΝΙΤΗΣ ΤΡΙΑΝΤΑΦΥΛΛΟΣ Ε. (Μνήμων, 2004)
Triantaphyllos E. Sklavenitis, The Fate of Korais’s Letter of 5 September 1816. (Molière, Kokkinakis, Skylitsis and the lithographer) In response to Adamantios Korais’s suggestion that Tartuffe should be translated into Modern Greek, Konstantinos Kokkinakis translated the play, had it printed in 1815 and sent a copy to Korais for his comments. Korais set out his opinion on the translation, with critical comments, in a long letter to Kokkinakis dated 5 September 1816. In 1851 Ioannis Isidoridis Skylitsis published his own translation of Tartuffe in Smyrna and after twenty years, in 1871, republished it in a reviewed form. Both in his prefatory notes and in his translation, Skylitsis repudiated Korais’s condemnation of rhyming verse, and he also rejected Kokkinakis’s decision to adhere as closely as possible to Moliere’s words: instead, he followed the example of Konstantinos Oikonomos, who had made a free translation of L’Avare in 1816. However, in 1871’s edition Skylitsis put as a frontispiece a fascimile lithograph of 1816’s letter in honour of Korais’s opinions despite the fact that he disagreed with them.